2019
DOI: 10.1111/aogs.13787
|View full text |Cite
|
Sign up to set email alerts
|

Provision of immediate postpartum intrauterine contraception after vaginal birth within a public maternity setting: Health services research evaluation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abstract Introduction: Expanding access to postpartum intrauterine contraception (PPIUC) can reduce unintended pregnancies and short inter-pregnancy intervals; however, provision across Europe is limited. Our aim was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 18 publications
3
32
3
Order By: Relevance
“…Method continuation in the current study was found to be high (86%) at one year of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks post-delivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 82%
“…Method continuation in the current study was found to be high (86%) at one year of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks post-delivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 82%
“…Method continuation in the current study was found to be high (86%) at 12 months of follow-up which is comparable or better than the 55-82% commonly reported by many other published studies [3,20,[27][28][29][30][31]. Moreover, the most vulnerable period for PPIUD discontinuation was that period after the puerperium to six months of delivery (i.e., 43-180 days) contrary to the period of up to 6 weeks postdelivery that is reported to be critical for IUD related complications and removal in some earlier studies [32,33].…”
Section: Discussionsupporting
confidence: 83%
“…However, unmet need for family planning is high in the postpartum period, ranging from 32 to 62% in low and middle- income countries [ 3 , 7 , 8 ]. Because of unmet need, unintended pregnancy is common in postpartum period [ 9 , 10 ]. Beside this closely spaced pregnancies are expected to have adverse maternal, perinatal and infant outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%